The innovator's dilemma : when new technologies cause great firms to fail - Christensen, Clayton M. (Management of innovation and change series., 2016)
"Offering both successes and failures from leading companies as a guide, The Innovator's Dilemma gives you a set of rules for capitalizing on the phenomenon of disruptive innovation"--Amazon.com.